IMPACTS OF RISING ANIMAL FOOD PRICES ON DEMAND AND POVERTY IN INDONESIA - Nikmatul Khoiriyah; Ratya Anindita; Nuhfil Hanani; Abdul Wahib Muhaimin (Agricultural Socio-Economics Journal, 2020)
Protein deficiency is one of the causes of the poor nutritional status of the Indonesian population, is permanent, and long-term will have an impact on the lower quality of human resources. This study analyzes the impact of price and income changes on animal food consumption patterns and demand on five poverty level in Indonesia. The demand esimation uses Quadratic Almost Ideal Demand Systems, using the National Socio Economic Survey (SUSENAS) data (March 2016) compilation data of 291,414 households. The results showed that there were different interactions between beef and the other four animal protein food sources, namely the Poor, Almost Poor and Vulnerable Poor beef substitution was mainly chicken, followed by fresh fish and eggs. Hicksian's own-price elasticity decreases following the decrease in the level of household poverty. Cases of beef, household own-price elasticity "extremely poor" -11.70% and "not poor" -1.95%. The sensitivity of the decrease in beef consumption is due to an increase in own-prices for "extremely poor" households 5.5 times compared to "non-poor". Beef is a very luxurious and relatively inaccessible source of animal protein food, especially for extremely poor, poor, almost poor, and vulnerable poor households, and this constitutes 40% of Indonesia's population. To increase beef consumption, it is necessary to increase domestic beef production so that the price of beef is affordable not only for non-poor households but also for extremely poor, poor, almost poor and vulnerable poor households in Indonesia